PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN PROSES FISIKA SISWA - Arika '; Muhammad Nasir Nasir; Fakhruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was to determine the effectiveness of the improvement Physics process skills in the class X1 and X2 Seri Rama YLPI Senior High School Pekanbaru application Discovery Learning model in geometrical optics materials. The research was conducted from March 2015 until June 2015 by research subjects 38 students in class X1 and 27 students in other. This research is the pre-experimental design Intact Group comparasion, with the class X1 as an experimental class and class X2 as the control class. The research instrument used is Physics process skills achievement test arrange of aspect: observing, predicting, communicating and classifying. The results of the research indicated of all aspect 81% in good categories and efectively in the class X1 and other hand 69% in good enough category and enough effectively. As conclution application of Discovery Learning model can improve the Physics process skills of student Seri Rama YLPI Senior High School Pekanbaru. Keywords: Discovery Learning, process skills, geometrical optics.